2003
DOI: 10.1029/2002jd003325
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term erythemal UV doses at Sodankylä estimated using total ozone, sunshine duration, and snow depth

Abstract: [1] A method for estimating daily erythemal UV doses using total ozone, sunshine duration, and snow depth has been developed. The method consists of three steps: (1) daily clear-sky UV doses were simulated using the UVSPEC radiative transfer program, with daily values of total ozone as input data, (2) an empirical relationship was sought between the simulated clear-sky UV doses, the measured UV doses, and the duration of bright sunshine, and (3) daily erythemal UV doses were estimated using this relationship. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(70 citation statements)
references
References 32 publications
3
67
0
Order By: Relevance
“…However, our model provides RMS error ∼ 15 % for estimates of the daily erythemal dose. Lindfors et al (2003) found RMS error of ∼ 23 %. To determine how model (2) uncertainty influences trend estimates for the whole period 1983-2016, we propose a Monte Carlo methodology to derive the trend value and its uncertainty based on a hypothetical bootstrap sample (N = 10 000) of the linear trend coefficients and their errors (see Sect.…”
Section: Data Reconstructionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our model provides RMS error ∼ 15 % for estimates of the daily erythemal dose. Lindfors et al (2003) found RMS error of ∼ 23 %. To determine how model (2) uncertainty influences trend estimates for the whole period 1983-2016, we propose a Monte Carlo methodology to derive the trend value and its uncertainty based on a hypothetical bootstrap sample (N = 10 000) of the linear trend coefficients and their errors (see Sect.…”
Section: Data Reconstructionmentioning
confidence: 99%
“…Table 1 shows the monthly bias and RMS errors of the model (3) performance for March-September in the period 2005-2016. The model setup is similar to that used by Lindfors et al (2003) for UV daily-dose reconstruction for Sodankylä. However, our model provides RMS error ∼ 15 % for estimates of the daily erythemal dose.…”
Section: Data Reconstructionmentioning
confidence: 99%
“…Lindfors et al, 2003;Den Outer et al, 2005;Lindfors and Vuilleumier, 2005;Reuder and Koepke, 2005). To the knowledge of the authors no study on the reconstruction of UV levels in a high alpine region above 3000 m has been performed.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we used ancillary data including global radiation (300-3000 nm) measured with a Kipp and Zonen CM11 pyranometer, sunshine duration measured with an electronic sunshine recorder (Lindfors et al, 2003) and SYNOP cloud amount. Figure 1 shows MODIS derived AOD values at 0.55 µm during a four-week-period for Tõravere as well as for Helsinki and Jokioinen in Finland.…”
Section: Surface Observations At Jokioinenmentioning
confidence: 99%